Effectiveness of room-of-error interventions for healthcare providers: a systematic review - Su Jin Jung; Jiwon Kang; Youngjin Lee (BMC Nursing)
Abstract Background Patient safety incidents are recognized as significant contributors to patient mortality, thus demanding immediate attention and strategic interventions in healthcare systems. The room-of-error education program serves as a solution, as it provides a case-based learning platform allowing nursing students to identify and resolve medical errors within a controlled environment systematically. This study aimed to identify the context, mechanisms, and outcomes of room-of-error training programs. Methods This study adopted a systematic review methodology aligning with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Comprehensive searches were conducted across key databases, including OvidMEDLINE, Embase, Cochrane, and CINAHL, by utilizing specific terms related to healthcare providers, nursing students, room-of-error education, medical errors, simulation training, and virtual intervention. Included studies focused on healthcare providers or students, error recognition, RFE-related training, and randomized or quasi-experimental trials, while exclusion criteria were non-English/Korean studies, non-original articles, abstracts, and qualitative studies. Risk of bias in the selected studies was assessed using the Risk Of Bias In Non-randomized Studies version 2.0 tool. Results The search strategy yielded 2,447 articles, with eight studies meeting the inclusion criteria. Predominantly quasi-experimental in design, these eight studies primarily focused on nurses as the target population. Simulations were found to be widely integrated into room-of-error programs, emphasizing skill performance and critical thinking. Half of the studies provided preparation time, 37.5% included feedback, and 62.5% covered medication errors, with 87.5% using offline delivery, 62.5% offering individual education, and program durations ranging from 4 to 35 min, with 25% having no time limit for error inspection. Diverse content, including topics such as medication errors and infection control, was found to be delivered through offline or virtual formats and group-based or individual education. Conclusions The findings provide valuable insights into the characteristics and outcomes of room-of-error training programs for healthcare professionals and students. This study emphasizes the significance of practical, case-based approaches in nursing education to augment knowledge, confidence, and competencies, thereby enhancing patient safety in clinical practice.